Cationic PEGylated polycaprolactone nanoparticles carrying post-operation docetaxel for glioma treatment - Varan, Cem; Bilensoy, Erem (Beilstein Journal of Nanotechnology, 2017)
Background: Brain tumors are the most common tumors among adolescents. Although some chemotherapeutics are known to be effective against brain tumors based on cell culture studies, the same effect is not observed in clinical trials. For this reason, the development of drug delivery systems is important to treat brain tumors and prevent tumor recurrence. The aim of this study was to develop core–shell polymeric nanoparticles with positive charge by employing a chitosan coating. Additionally, an implantable formulation for the chemotherapeutic nanoparticles was developed as a bioadhesive film to be applied at the tumor site following surgical operation for brain glioma treatment. To obtain positively charged, implantable nanoparticles, the effects of preparation technique, chitosan coating concentration and presence of surfactants were evaluated to obtain optimal nanoparticles with a diameter of less than 100 nm and a net positive surface charge to facilitate cellular internalization of drug-loaded nanoparticles. Hydroxypropyl cellulose films were prepared to incorporate these nanoparticle dispersions to complete the implantable drug delivery system.Results: The diameter of core–shell nanoparticles were in the range of 70–270 nm, depending on the preparation technique, polymer type and coating. Moreover, the chitosan coating significantly altered the surface charge of the nanoparticles to net positive values of +30 to +50 mV. The model drug docetaxel was successfully loaded into all particles, and the drug release rate from the nanoparticles was slowed down to 48 h by dispersing the nanoparticles in a hydroxypropyl cellulose film. Cell culture studies revealed that docetaxel-loaded nanoparticles cause higher cytotoxicity compared to the free docetaxel solution in DMSO.Conclusion: Docetaxel-loaded nanoparticles dispersed in a bioadhesive film were shown to be suitable for application of chemotherapeutics directly to the action site during surgical operation. The system was found to release chemotherapeutics for several days at the tumor site and neighboring tissue. This can be suggested to result in a more effective brain tumor treatment when compared to chemotherapeutics administered as an intravenous bolus infusion.
Keywords: bioadhesive film; cationic nanoparticle; core–shell nanoparticle; docetaxel; glioma